Hieracium moravense (Asteraceae), a new hawkweed from Albania - Gottschlich, Günter; Selvi, Federico (Phytotaxa, 2023)
Hieracium moravense, a new hawkweed from the ultramafic soils of the region of Korcë in Albania, is described and illustrated.